Physiological Characteristics of Incoming Freshmen Field Players in a Men’s Division I Collegiate Soccer Team - Robert G. Lockie; DeShaun L. Davis; Samantha A. Birmingham-Babauta; Megan D. Beiley; Jillian M. Hurley; Alyssa A. Stage; John J. Stokes; Tricia M. Tomita; Ibett A. Torne; Adrina Lazar (Sports, 2016)
Freshmen college soccer players will have lower training ages than their experienced teammates (sophomores, juniors, seniors). How this is reflected in field test performance is not known. Freshmen (n = 7) and experienced (n = 10) male field soccer players from the same Division I school completed soccer-specific tests to identify potential differences in incoming freshmen. Testing included: vertical jump (VJ), standing broad jump, and triple hop (TH); 30-m sprint, (0–5, 5–10, 0–10, and 0–30 m intervals); 505 change-of-direction test; Yo-Yo Intermittent Recovery Test Level 2 (YYIRT2); and 6 × 30-m sprints to measure repeated-sprint ability. A MANOVA with Bonferroni post hoc was conducted on the performance test data, and effect sizes and z-scores were calculated from the results for magnitude-based inference. There were no significant between-group differences in the performance tests. There were moderate effects for the differences in VJ height, left-leg TH, 0–5, 0–10 and 0–30 m sprint intervals, and YYIRT2 (d = 0.63–1.18), with experienced players being superior. According to z-score data, freshmen had meaningful differences below the squad mean in the 30-m sprint, YYIRT2, and jump tests. Freshmen soccer players may need to develop linear speed, high-intensity running, and jump performance upon entering a collegiate program.